(untitled) (Communications in Computational Physics, 2010)
In this paper, we investigate by numerical simulations the Bak-Sneppen model (BSM) for biological evolution on scale-free networks (SFNs) with various degree exponents γ. We find that the punctuated equilibrium is rather robust with respect to the network topology. Furthermore, we analyze the evolution of the critical average fitness ∗ and the exponent τ of 0 avalanche as a function of α (i.e., the degree exponent γ). Our observations indicate the dependence of evolutionary dynamics of BSM on the complex biosystem topology.